Removable Partial Denture Design using Milled Surface as a Precision Attachment: An Esthetic Alternative - Prasad, Krishna D; Hegde, Chethan; Shah-Naidu, Namrata G; Shetty, Manoj (Journal of Orofacial Research, 2012)
This case report describes the combined use of fixed partial denture prosthesis (FPD) and removable partial denture prosthesis (RPD) for a patient with partially edentulous arches and few remaining teeth. The RPD was designed such that it would take advantage of the benefits from milled palatal surfaces of the FPD to enhance stability and retention of the RPD and allow maintenance of optimum oral hygiene.